Knowledge Management And Academic Library Performance: A Framework - Che Jaafar, Cik Ramlah; Fesal, Fujica Azura; Ibrahim, Intan Haryati (2013)
The role of knowledge as a valuable resource to the organization has been recognized by academicians and practitioners. For that reasons knowledge management (KM) has been introduced to help organization managing the knowledge systematically and effectively. KM has been widely practiced by many organizations including academic library in order to improve the organization’s performance. In this 21st century, KM has become an essential mechanism for library organizations to provide a dynamic and effective service to library users. This paper reviews the concepts of KM and library performance and proposes a framework for further research. The paper tries to establish a relationship between KM and library performance that will be beneficial for the academic library.